An integrated approach to quantitative modelling in angiogenesis research - Connor, AJ; Nowak, RP; Lorenzon, E; Thomas, M; Herting, F; Hoert, S; Quaiser, T; Shochat, E; Pitt-Francis, J; Cooper, J; Maini, PK; Byrne, HM (Royal Society, 2015)
Angiogenesis, the process by which new vessels form from existing ones, plays an important role in many developmental processes and pathological conditions. We study angiogenesis in the context of a highly controllable experimental environment: the cornea micropocket assay. Using a multidisciplinary approach that combines experiments, image processing and analysis, and mathematical modelling, we aim to provide mechanistic insight into the action of two angiogenic factors, vascular endothelial growth factor A (VEGF-A) and basic fibroblast growth factor (bFGF). We use image analysis techniques to extract quantitative data, which are both spatially and temporally resolved, from experimental images, and we develop a mathematical model, in which the corneal vasculature evolves in response to both VEGF-A and bFGF. The experimental data are used for model parametrization, while the mathematical model is used to assess the utility of the cornea micropocket assay and to characterize proposed synergies between VEGF-A and bFGF.